425PEconomic and safety evaluation of 5-HT3 recepter antagonist conversion from palonosetron to granisetron in highly and moderately emetogenic chemotherapy: A prospective study. (24th November 2019) - Yamakita, K; Kitano, Y; Suzuki, Y; Iwamoto, H; Takahashi, K; Ota, T
Abstract: Background: Palonosetron (PALO) is a second-generation 5-hydroxytryptamine 3 receptor antagonist (5HT3RA) that has shown better efficacy than first-generation 5HT3RA (granisetron; GRA) in preventing chemotherapy-induced nausea and vomiting (CINV). PALO is usually administrated repeatedly when the patients have no nausea even though it is expensive as compared with GRA. However, we could reduce medical costs for chemotherapy if 5HT3RA conversion from PALO to GRA in the patient without having CINV is safe and tolerable. Methods: We prospectively investigated patients receiving highly or moderately emetogenic chemotherapy (HEC or MEC) in combination with PALO for digestive organ cancers in accordance with guideline of Japan Society of Clinical Oncology. Patients assessed as complete response (CR) during the acute phase (0-24 h postchemotherapy) and the delayed phase (24-120 h postchemotherapy) in consecutive treatments were converted their antiemetic agents from PALO to GRA. We evaluated the incidence of CINV and the cost-effectiveness. Results: Thirty five cases (madian age 73 years, female 51.4%, 18; pancreatic cancer, 8; colorectal cancer, 3; esophageal cancer, 3; gastric cancer, 3; biliary tract cancer) were enrolled at our institution between January 2018 and June 2019. Ten cases were administrated HEC (HEC group) and 25 cases were administrated MEC (MEC group). One case of HEC group and 2 cases of MEC group changed their chemotherapy regimens due to adverse events and progression of disease. Four cases of HEC group (40.0%) and 14 cases of MEC group (56.0%) were assessed as CR in consecutive treatments, thereafter their antiemetic agents were converted from PALO to GRA in the subsequent treatments. All of them continued their chemotherapy without the incidence of nausea and vomiting. Among the cases assessed as CR, we could save 111, 935 Japanese yen (1, 034.6 USD, range, 13, 868-194, 152 JPY) per case by conversion of 5HT3RA. Conclusions: Our data indicated that the conversion of 5HT3RA is safe and also provide economic benefit in patients receiving HEC or MEC. When patients receiving HEC or MEC with PALO were assessed as CR, we should consider conversion of 5HT3RA. Legal entity responsible for the study: Asahikawa medical University. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.